Interaction of Galectin-3 Concentrations with the Treatment Effects of β-Blockers and RAS Blockade in Patients with Systolic Heart Failure: A Derivation-Validation Study from TIME-CHF and GISSI-HF. (6th January 2020) - Wijk, Sandra Sanders-van; Masson, Serge; Milani, Valentina; Rickenbacher, Peter; Gorini, Marco; Tavazzi, Luigi T; Tobler, Daniel; Rickli, Hans; Latini, Roberto; Brunner-La Roccaenen, Hans-Peter; ,
Abstract: BACKGROUND: Galectin-3 predicts prognosis in heart failure (HF) and may help to select HF patients in need of intensified therapy. METHODS: This retrospective post hoc analysis included 219 patients from the Trial of Intensified versus Standard Medical Therapy in Elderly Patients with Congestive Heart Failure (TIME-HF) and 631 patients from Gruppo Italiano per lo Studio della Sopravvivenza nell'Insufficienza Cardiaca (GISSI-HF) with HF who had reduced ejection fraction and available galectin-3 plasma concentrations. The interaction between galectin-3, β-blockers, renin-angiotensin system (RAS) blockade, and spironolactone on outcome was evaluated in TIME-CHF and validated in GISSI-HF. End points were all-cause mortality and the composite of mortality with HF hospitalization or any hospitalization. RESULTS: High galectin-3 concentrations were associated with adverse outcome in both cohorts and remained significantly associated with death after multivariate adjustment [hazard ratio 2.42 (95% CI 1.17–5.01), P = 0.02, in TIME-CHF; 1.47 (1.02–2.10), P = 0.04, in GISSI-HF). In TIME-CHF, patients with low galectin-3 plasma concentrations had a better prognosis when β-blockers were up-titrated, whereas patients with high galectin-3 plasma concentrations did not (interaction P < 0.05 for mortality and death with or without hospitalization). Opposite trends were seen for RAS blockade but were not statistically significant. Patients with high galectin-3 plasma concentrations had neutral prognosis when receiving spironolactone, whereas patients with low galectin-3 plasma concentrations had worse prognosis when receiving spironolactone (interaction P < 0.10 for death with or without hospitalization). In the GISSI-HF validation cohort, these interactions were confirmed for β-blockers ( P < 0.05 for all end points) and consistent for RAS blockade ( P < 0.10 for death with or without hospitalization), but inconsistent for spironolactone. CONCLUSIONS: Galectin-3 is a mediocre prognostic marker, and galectin-3 concentrations interact with the treatment effect of β-blockers and possibly RAS blockade in patients with systolic HF.